Reporting on 16 years of laboratory capacity building while exploring the future of WOAH's Laboratory Twinning Programme - Marrana, Mariana; Appiah, Emmanuel; Jeannin, Morgan; Gilbert, William; Nilsson, Adriana; Hamilton, Keith; Rushton, Jonathan (Frontiers in Veterinary Science, 2022)
Animal health laboratories are an increasingly important part of safeguarding animal and public health due to their role in surveillance and diagnostics of animal diseases, food safety, and in the development and production of medicinal products, vaccines, and diagnostic tools. Despite their importance, the global distribution of veterinary laboratory expertise is uneven, with greater concentration of reference laboratories in wealthier countries. To address this issue, the World Organisation for Animal Health (WOAH, founded as OIE) created a Laboratory Twinning Programme in 2006. The paper will briefly review this Programme in the context of an increasingly populated global health security field, based on a literature review and on a combination of public and internal WOAH data and describe the implementation of the Programme in the past 16 years, noting the drivers for project implementation, its links with the global livestock biomass distribution and with the current distribution of veterinary laboratory expertise. There has been broad uptake and diversity in the focus of the twinning projects implemented in WOAH Member Countries. The Laboratory Twinning Programme would benefit from an evaluation that looks at its outcomes and quantifiable impact in beneficiary countries. A case is made for the development of a monitoring and evaluation system tailored to the Programme’s specificities.